Evaluation of the effect of dental caries, oral hygiene, and treatment need on oral health-related quality of life among Turkish orphan children and adolescents - Ecem Akbeyaz Şivet; Berkant Sezer; Neslihan Atmaca; Narmin Hüseynova; Betül Kargül (BMC Oral Health)
Abstract Background The oral and dental health and related quality of life of orphan children and adolescents—who are considered a vulnerable population—are critical for both individual and public health. Objectives This study aimed to investigate the status of the dental caries, oral hygiene, and dental treatment needs among a group of Turkish male orphan children and adolescents, as well as their impact on oral health-related quality of life. Methods A total of 112 orphan children and adolescents aged between 9 and 17 years living in a residential care facility in Istanbul, Türkiye, were involved in this cross-sectional study. A comprehensive examination was conducted on each individual, encompassing the assessment of dental caries using the decayed, missing, and filled teeth (DMFT/dft) index, oral hygiene using the debris (DI-S), calculus (CI-S), and simplified oral hygiene (OHI-S) indices, and dental treatment need using the treatment need index (TNI). Oral health-related quality of life was evaluated using the validated Turkish version of the Child Oral Health Impact Profile-Short Form (COHIP-SF-19). The relationship between oral health-related quality of life and explanatory variables was evaluated using a multivariable linear regression model. Results The mean age of the participants was 12 ± 1.79 years. The mean DMFT score was 4.57 ± 3.42, and the mean OHI-S score was 1.4 ± 0.52. Participants had a mean COHIP-SF-19 score of 57.79 ± 14.11, with 25% requiring at least one tooth to undergo radical treatment. Multivariable linear regression analysis indicated that the DMFT score (p = 0.009) and the need for radical treatment (TNI code 6) (p < 0.001) had a statistically significant impact on oral health-related quality of life among orphan children and adolescents aged 13–17. Conclusions This study underscores that dental caries and the need for radical treatment significantly impact the oral health-related quality of life of orphan children and adolescents.